Learning by Using Traditional Children's Games "Sesiku" in Developing Early Childhood Character Values - Evi Selva Nirwana (AL-ISHLAH: Jurnal Pendidikan, 2021)
The research objective was to examine learning plans, learning activities, and the impact of learning by using traditional games sesiku in building character values in Kindergartens in Bengkulu City. The children's character values that emerge from the traditional games sesiku are the character values of honesty, discipline, sportsmanship, cooperation, and help. The method used in this study was experimental. The instrument for the observation of character values was tested on 30 children aged 5-6 years. The validity used the character value of the observation guideline sheet with product-moment correlation and the reliability of the character value of the observation guideline sheet with Cronbach's Alfa. The T-test is used to see a significant difference between the two average parameters in the same sample group between the initial and final test scores. The research findings indicated that the format of the daily learning implementation plan had followed the appropriate format. The learning process integrates Bengkulu's traditional children's games into early activities outside the classroom. Bengkulu's traditional children's games are internalized into the lesson plan and teacher's lesson plan to contribute to developing character values in early childhood. In the teaching and learning process and after the end of the teaching and learning process, the character values of children can be observed from the behavior that appears, such as the character values of honesty, discipline, sportsmanship, cooperation, and help.